Soviet Occupation Actions to Demoralise and Break up Lithuanian Resistance in the Summer of 1945 - Kasparas, Kęstutis (Genocidas ir rezistencija, 1998)
In the summer of 1945, the Russian occupiers were not planning to change their tactics in suppressing military resistance in Lithuania. The most important means of suppression was, as before, the military force of the NKVD and NKGB. The partisans were demoralised by the amnesty and the possibility of legalising their status offered by the occupiers. The Soviet propaganda portrayed the LSSR government’s address to the Lithuanian nation on 9 February 1945, promising to ‘pardon’ the ‘wrongs’ of the resistance participants, as a very humane act aimed at putting an end to the senseless blood shedding and at saving the people. This propaganda image was later repeated in historical papers and the press, claiming that the collaborators were peaceful and caring about the fate of the nation (national communism), while the alien Stalinists, who preferred military and terror measures, were nothing but dullards.